Service Management in Non-Communicable Disease Prevention Regulations in the Perspective of Public Value Management (Study at Singosari Health Center Malang Regency) - Athiyyah Putri Andini (Faculty of Law, Universitas Pekalongan, 2025)
Management of non-communicable disease (NCD) prevention services is one of the major challenges in the current public health system, especially at the primary service level such as the Health Center at the Singosari Health Center, Malang Regency, various NCD prevention efforts have been carried out, but there is still a gap between program policies and their implementation in the field. This study aims to analyze management service prevention PTM in Health Center The Lion City Malang Regency through three main aspects: public value, legitimacy and support, and operational efficiency. This study uses a qualitative approach with a data collection method in the form of interviews which aims to gather information about the description of the implementation of disease prevention service management. The results of interviews with five informants showed that the community was quite satisfied with the services provided, especially screening and early detection. This program has received support from various parties, including the Health Office and local government. However, there are still challenges in the form of a lack of evaluation systems, limited facilities, and low public awareness. Strengthening cross-sector collaboration and utilizing technology is needed to increase the effectiveness of the program.